PENGEMBALIAN KERUGIAN NEGARA DALAM TINDAK PIDANA KORUPSI MELALUI PEMBAYARAN UANG PENGGANTI DAN DENDA - Guntur Rambey (Universitas Muhammadiyah Sumatera Utara, 2016)
Corruption is one of the biggest problems faced by several countries, including Indonesia, that transform and eradicate corruption efforts are being made by various methods as well. In Indonesia, one of the efforts is the presence of additional criminal penalties for perpetrators of corruption in the form of indemnification of the country through the payment of restitution and fines. This effort is expected to be able to restore financial losses or the economy. Countries corrupted by criminals because basically the state's losses in terms of money it should be done so that the perpetrators of corruption are not only sentenced to imprisonment but there should be an attempt to impoverish the corruptors.